Inhibition of the NLRP3/IL‐1β axis protects against sepsis‐induced cardiomyopathy. Issue 6 (2nd September 2021) - Busch, Katharina; Kny, Melanie; Huang, Nora; Klassert, Tilman E.; Stock, Magdalena; Hahn, Alexander; Graeger, Sebastian; Todiras, Mihail; Schmidt, Sibylle; Chamling, Bishwas; Willenbrock, Michael; Groß, Stefan; et al.
Abstract: Background: Septic cardiomyopathy worsens the prognosis of critically ill patients. Clinical data suggest that interleukin‐1β (IL‐1β), activated by the NLRP3 inflammasome, compromises cardiac function. Whether or not deleting Nlrp3 would prevent cardiac atrophy and improve diastolic cardiac function in sepsis was unclear. Here, we investigated the role of NLRP3/IL‐1β in sepsis‐induced cardiomyopathy and cardiac atrophy. Methods: Male Nlrp3 knockout (KO) and wild‐type (WT) mice were exposed to polymicrobial sepsis by caecal ligation and puncture (CLP) surgery (KO, n  = 27; WT, n  = 33) to induce septic cardiomyopathy. Sham‐treated mice served as controls (KO, n  = 11; WT, n  = 16). Heart weights and morphology, echocardiography and analyses of gene and protein expression were used to evaluate septic cardiomyopathy and cardiac atrophy. IL‐1β effects on primary and immortalized cardiomyocytes were investigated by morphological and molecular analyses. IonOptix and real‐time deformability cytometry (RT‐DC) analysis were used to investigate functional and mechanical effects of IL‐1β on cardiomyocytes. Results: Heart morphology and echocardiography revealed preserved systolic (stroke volume: WT sham vs. WT CLP: 33.1 ± 7.2 μL vs. 24.6 ± 8.7 μL, P  < 0.05; KO sham vs. KO CLP: 28.3 ± 8.1 μL vs. 29.9 ± 9.9 μL, n.s.; P  < 0.05 vs. WT CLP) and diastolic (peak E wave velocity: WT sham vs. WT CLP: 750 ± 132 vs. 522 ± 200 mm/s, P  < 0.001; KO sham vs. KO CLP: 709 ± 152 vs. 639 ± 165 mm/s, n.s.; P  < 0.05 vs. WT CLP) cardiac function and attenuated cardiac (heart weight–tibia length ratio: WT CLP vs. WT sham: −26.6%, P  < 0.05; KO CLP vs. KO sham: −3.3%, n.s.; P  < 0.05 vs. WT CLP) and cardiomyocyte atrophy in KO mice during sepsis. IonOptix measurements showed that IL‐1β decreased contractility (cell shortening: IL‐1β: −15.4 ± 2.3%, P  < 0.001 vs. vehicle, IL‐1RA: −6.1 ± 3.3%, P  < 0.05 vs. IL‐1β) and relaxation of adult rat ventricular cardiomyocytes (time‐to‐50% relengthening: IL‐1β: 2071 ± 225 ms, P  < 0.001 vs. vehicle, IL‐1RA: 564 ± 247 ms, P  < 0.001 vs. IL‐1β), which was attenuated by an IL‐1 receptor antagonist (IL‐1RA). RT‐DC analysis indicated that IL‐1β reduced cardiomyocyte size ( P  < 0.001) and deformation ( P  < 0.05). RNA sequencing showed that genes involved in NF‐κB signalling, autophagy and lysosomal protein degradation were enriched in hearts of septic WT but not in septic KO mice. Western blotting and qPCR disclosed that IL‐1β activated NF‐κB and its target genes, caused atrophy and decreased myosin protein in myocytes, which was accompanied by an increased autophagy gene expression. These effects were attenuated by IL‐1RA. Conclusions: IL‐1β causes atrophy, impairs contractility and relaxation and decreases deformation of cardiomyocytes. Because NLRP3/IL‐1β pathway inhibition attenuates cardiac atrophy and cardiomyopathy in sepsis, it could be useful to prevent septic cardiomyopathy.